Faktor Ekonomi Dan Sosial Yang Mempengaruhi Pemberdayaan Gender - Yustie, Renta; Prayitno, Budi (Equilibrium: Jurnal Ekonomi-Manajemen-Akuntansi, 2024)
Gender is one of the important issues and current discussions in North Kalimantan Province. This is indicated by the contribution of women as workers in North Kalimantan who still lack participation with the gender empowerment index being in the range of 50 to 60. Focusing on the role and function of women in society and government in their contribution to the regional economy of North Kalimantan Province, it is necessary to increase the active role of women. The role and function of women is measured by 3 (three) factors, namely the presence of women in parliament, women in professional staff, women's income so that these three factors are independent variables in the research, which will influence the gender empowerment factor which is used as the dependent variable in this research. Developing and balanced gender empowerment can formally increase the role and position of women workers in society and encourage sustainable development in North Kalimantan Province. This research is quantitative research with secondary data sourced from BPS North Kalimantan Province. The research sample used 5 districts/cities in North Kalimantan Province, namely Kab. Malinau, Kab. Bulungan, Kab. Tana Tidung, Kab. Nunukan, Tarakan City. The research method uses a panel method for the period 2017 to 2022, with a panel data multiple linear regression model. The analytical tool used to calculate research data is Eviews 10. The alpha (α) value in the research is 5% or equivalent to 0.05 and the result is that all independent variables in the research are able to influence the dependent variable, namely the gender empowerment index to improve the role and position of the workforce. women and encourage sustainable development in North Kalimantan Province in the long term and support SDG's point 5, namely gender equality.